Tenebrio molitor (Coleoptera: Tenebrionidae)-Optimization of Rearing Conditions to Obtain Desired Nutritional Values - Adámková, Anna; Mlček, Jiří; Adámek, Martin; Borkovcová, Marie; Bednářová, Martina; Hlobilová, Veronika; Knížková, Ivana; Juríková, Tunde (Journal of insect science (Online), 2020)
The present study dealt with the influence of temperature and feed on the nutritional value of Tenebrio molitor, especially on the content of crude protein, amino acids, fat, and fatty acid profile. Tenebrio molitor larvae were kept in 15, 20, and 25°C and fed with wheat bran, lentil flour, and mixture. The parameters were analyzed by international standard methods. Generally, with an increase of the lentils in the feed, the crude protein content increased. The changes in the temperature and the feed were most pronounced on the essential amino acids Val, Arg, and Leu. The highest average fat content was determined at 20°C in insects fed with wheat bran. The lowest fat content was determined at 15°C in bran-fed insects. The dependency of fat content on the temperature in feeding with lentil flour and a mixture of wheat bran and lentil flour was statistically insignificant (P > 0.05, Kruskal-Wallis, Mann-Whitney post hoc tests). The highest content of polyene fatty acids was achieved at a rearing temperature of 15°C and the bran diet. It was concluded that a higher proportion of protein diet could increase the content of crude protein in the insects. An increase in the temperature generally leads only to a slight increase in the content of nitrogenous substances. The influence of feed on this nutritional parameter is therefore much more significant than the effect of the rearing temperature. In general, it can be stated that the feed and the temperature also significantly affect the fat content.
Keywords: nutritional value; brouci; teplota; Tenebrio; mealworm; nutriční hodnota; Animals; lentil flour; Nutritive Value; Temperature; zvířata; Diet; temperature; dieta; wheat bran; Coleoptera